Individuazione e implementazione di indicatori di benessere animale: aspetti tecnici e impatto economico - Fabio Gaetano Santeramo; Marzia Albenzio; Maria Giovanna Ciliberti; Emilia Lamonaca; Marco Tappi; Mariangela Caroprese; Leonardo Di Gioia (Italian Review of Agricultural Economics (REA), 2020)
– The planning of a policy intervention aims at optimizing the decision-making process, resources allocation, outcomes of the intervention. The development of an integrated approach may contribute to achieve an effective and efficient planning. The article develops a protocol based on the adoption of qualitative and quantitative methods, in order to support policymaker in planning intervention measures. The developed protocol is tested on a case study: the planning of measure 14 - Animal welfare - in the Rural Development Programme 2014-2020 of the Apulia region. Indicators of animal welfare, scientifically valid and objectively miserable, emerged from the case study as additional commitments to implement in cattle and buffalo farms. An economic analysis of each indicators allowed to estimate a countervailing measure for additional costs associated with the achievement of higher standards of animal welfare.
Keywords: P25; Q18; R58; 330; benessere animale; pianificazione; programma di sviluppo rurale; triangolazione metodologica